The therapeutic potential of Myoki, a novel peptide in muscle atrophy: mechanisms and applications - Kim, Eun Mi; Kim, Seon Soo; Hyun, Yong Geon; Lee, Su Yeon; Chung, Yong Ji (Frontiers in Pharmacology, 2026)
BackgroundWith the global population rapidly aging, the prevalence of sarcopenia, referring to a progressive loss of skeletal muscle mass and strength, is increasing, highlighting the need for effective preventive and therapeutic strategies. In this study, we evaluated the efficacy of Myoki, a synthetic peptide, in muscle atrophy models in vitro, in vivo, and in a human clinical trial.MethodsThis study evaluated the therapeutic potential of Myoki, a synthetic peptide, in preventing muscle atrophy by assessing its effects in multiple models. In vitro, C2C12 myoblasts were used to evaluate Myoki’s impact on cytotoxicity, myotube differentiation, and muscle atrophy in DEX-induced atrophy models, with effects measured by western blot, qRT-PCR, and immunofluorescence. The binding affinity between Myoki and myostatin was further evaluated using surface plasmon resonance (SPR) and confirmed by ELISA-based assays. In vivo, the accelerated aging mouse model (SAMP8) was employed to investigate Myoki’s effect on muscle fiber area, collagen deposition, and muscle atrophy markers, with muscle histology, fibrosis, and fluorescence intensities of key proteins assessed via immunofluorescence after 45 weeks of treatment. In the clinical study, a randomized, double-blind, placebo-controlled trial was conducted with 80 patients diagnosed with muscle atrophy, who received Myoki (200 mg/day) or placebo for 12 weeks. Key efficacy endpoints included changes in muscle mass (DEXA), handgrip strength, walking speed (6-m walk test), and serum marker levels, with safety monitored throughout the trial.ResultsMyoki demonstrated no cytotoxicity up to 500 μM in C2C12 cells and significantly promoted myotube differentiation. In DEX-induced muscle atrophy models, Myoki restored protein synthesis signaling and reduced muscle degradation pathways. In the SAMP8 mouse model, Myoki improved muscle fiber area, reduced collagen deposition, and mitigated muscle fibrosis. In the clinical trial, Myoki supplementation for 12 weeks significantly improved muscle mass, walking speed, and grip strength, along with favorable changes in serum markers related to muscle growth and damage.ConclusionOur results position Myoki as a promising potential candidate for mitigating muscle atrophy, including age-associated muscle loss. These findings support its therapeutic potential for conditions such as sarcopenia, making it a valuable candidate for further clinical exploration.Clinical Trial Registrationclinicaltrials.gov, CTRI/2024/01/061919.